Exploring an approach to transforming the traditional chinese cultural heritage into modern product design education: a case study of Yingjing Sand Vessels / Wang Ling, Siti Zuraida Maaruf and Xuemin You - Ling, Wang; Maaruf, Siti Zuraida; You, Xuemin (2024)
This study explores teaching approaches in design education focused on transforming traditional Chinese cultural heritage into modern product designs. It aims to develop a teaching model integrating traditional culture into product design education. The research examines the current state, main contents, theories, and principles of traditional culture integration into product design education. It then develops a basic teaching framework for integrating traditional culture into product design. Finally, the study uses design outcomes from project-based courses to collect data and analyse results. The research centres on a case study involving the redesign of the Yingjing Sand Vessel, a non-heritage vessel from Sichuan, China, within a design project-based course. Utilising Design Development Research (DDR), the Nominal Group Technique (NGT), a qualitative research methodology for data collection and document analysis. The outcomes of this study serve as a valuable exploration for developing a teaching model that fosters the integration of traditional culture into product design education and offers insights into enhancing the pedagogy and the societal impact of design courses in higher education.